Pengetahuan Orang Tua tentang Gangguan Perkembangan Speech Delay pada Anak Usia 1-5 Tahun di Posyandu Wilayah Kerja Puskesmas Sidomulyo Pekanbaru - Wiwik Norlita; Isnaniar; Mutiara Rizky (Fakultas MIPA dan Kesehatan, Universitas Muhammadiyah Riau, 2022)
Children’s growth and development is an important thing that must be considered. One of the developments in children is speaking and language according to their age. If there are developmental disorders such as speech delay in children will have an impact in the future on the children’s speech ability. The level of knowledge of parents plays an important role in the attitude and behavior of children in speech and language in everyday life. The Objective : To determine the Description Of Parents Knowledge Abouut Developmental Disorders : Speech Delay In Children Aged 1-5 Years at Posyandu Working Area Of Puskesmas Sidomulyo Pekanbaru. The Methods : This type of research is descriptive. The research was carried out on July 16 to 31, 2022 at Posyandu Sejahtera Putri Melur Pekanbaru with Accidental Sampling technique. The population in this study were all parents who visited Posyandu Sejahtera Putri Melur Pekanbaru with the number of respondents as many as 47 respondents. The instrument used was to distribute questionnaires to parents who visited Posyandu Sejahtera Putri Melur Pekanbaru. The Results : Showed that of the 47 respondents the majority of parents knowledge of developmental disorders speech delay in children aged 1-5 years have less knowledge with 22 respondents (46.8%), good knowledge as many as 12 respondents (25.5%), and sufficient knowledge as many as 13 respondents (27.7%). The Conclusiom : Knowledge of parents who visited Posyandu Sejahtera Putri Melur Pekanbaru about speech delay in children aged 1-5 years showed in the category of less influenced by age, education, information resources, experience and knowledge.